Educating seamlessly. From the integrated view of theories to the experiences of the Italian pedagogical community - Mangione, Giuseppina Rita; Di Tore, Pio Alfredo; Di Tore, Stefano; Corona, Felice (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2015)
The learning is no longer related to the structural setting of traditional classroom; it is instead an “across spaces” place characterized by the possibility to build ubiquitous experiences. Such experiences are in fact no more subject to space-time limits and bounds but focused on context – student relation and on situation awareness to enhance the learning processes. Also, these experiences are often associated with next generation technologies, mobiles, wereables and interactives, which well fit to a paradigm shift marked by learning situations in enactive, embodied and readable by the student learning. In this work, we present the first theoretical and applicative results that the Italian scientific community has achieved as part of the research lines that involve around the concept of Situation Awareness and Cognitive Awareness, constituent a seamless learning.